Protein evolution of Toll-like receptors 4, 5 and 7 within Galloanserae birds - Vinkler, Michal; Bainová, Hana; Bryja, Josef (Genetics, selection, evolution, 2014)
BACKGROUND: Toll-like receptors (TLR) are essential activators of the innate part of the vertebrate immune system. In this study, we analysed the interspecific variability of three TLR (bacterial-sensing TLR4 and TLR5 and viral-sensing TLR7) within the Galloanserae bird clade, investigated their phylogeny, assessed their structural conservation and estimated site-specific selection pressures. RESULTS: Physiochemical properties varied according to the TLR analysed, mainly with regards to the surface electrostatic potential distribution. The predicted ligand-binding features (mainly in TLR4 and TLR5) differed between the avian proteins and their fish and mammalian counterparts, but also varied within the Galloanserae birds. We identified 20 positively selected sites in the three TLR, among which several are topologically close to ligand-binding sites reported for mammalian and fish TLR. We described 26, 28 and 25 evolutionarily non-conservative sites in TLR4, TLR5 and TLR7, respectively. Thirteen of these sites in TLR4, and ten in TLR5 were located in functionally relevant regions. The variability appears to be functionally more conserved for viral-sensing TLR7 than for the bacterial-sensing TLR. Amino-acid positions 268, 270, 343, 383, 444 and 471 in TLR4 and 180, 183, 209, 216, 264, 342 and 379 in TLR5 are key candidates for further functional research. CONCLUSIONS: Host-pathogen co-evolution has a major effect on the features of host immune receptors. Our results suggest that avian and mammalian TLR may be differentially adapted to pathogen-derived ligand recognition. We have detected signatures of positive selection even within the Galloanserae lineage. To our knowledge, this is the first study to depict evolutionary pressures on Galloanserae TLR and to estimate the validity of current knowledge on TLR function (based on mammalian and chicken models) for non-model species of this clade.
Keywords: molekulární evoluce; Humans; Anseriformes; Computer Simulation; Protein Structure, Tertiary; Mice; zvířata; toll-like receptor 5; Binding Sites; Toll-Like Receptor 5; vazebná místa; počítačová simulace; sekvenční analýza proteinů; Sequence Analysis, Protein; Toll-Like Receptor 7; Toll-Like Receptor 4; myši; Evolution, Molecular; Animals; lidé; toll-like receptor 4; Galliformes; toll-like receptor 7; terciární struktura proteinů